2019
DOI: 10.1038/s41598-019-56612-7
|View full text |Cite|
|
Sign up to set email alerts
|

Genome mining and characterisation of a novel transaminase with remote stereoselectivity

Abstract: Microbial enzymes from pristine niches can potentially deliver disruptive opportunities in synthetic routes to Active Pharmaceutical Ingredients and intermediates in the Pharmaceutical Industry. Advances in green chemistry technologies and the importance of stereochemical control, further underscores the application of enzyme-based solutions in chemical synthesis. The rich tapestry of microbial diversity in the oceanic ecosystem encodes a capacity for novel biotransformations arising from the chemical complexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 92 publications
0
7
0
Order By: Relevance
“…Leveraging this characteristic, we devised a substrate analog screening strategy, employing the amination of cyclohexanone or its analogs as a model reaction to discover enzymes that can convert (−)-menthone to (+)-neomenthylamine. Subsequently, we screened 83 target enzymes from different sources capable of catalyzing amination reaction, including transaminases (TAs), imine reductases (IREDs), reductive amine enzymes (RedAms), amine dehydrogenases (AmDHs), and aminodeoxychorismate lyases (ADCLs) (Koszelewski et al 2011 ; Tufvesson et al 2012 ; Skalden et al 2015 ; Wetzl et al 2016 ; Guo and Berglund 2017 ; Ramsden et al 2019 ; Gavin et al 2019 ; Mangas-Sanchez et al 2020 ). After expressing and rescreening of the enzymes in the form of cell-free extract, we obtained a transaminase ( Vf TA) from Vibrio fluvialis JS17 (PDB: 5ZTX) that can convert (−)-menthone into (+)-neomenthylamine successfully.…”
Section: Resultsmentioning
confidence: 99%
“…Leveraging this characteristic, we devised a substrate analog screening strategy, employing the amination of cyclohexanone or its analogs as a model reaction to discover enzymes that can convert (−)-menthone to (+)-neomenthylamine. Subsequently, we screened 83 target enzymes from different sources capable of catalyzing amination reaction, including transaminases (TAs), imine reductases (IREDs), reductive amine enzymes (RedAms), amine dehydrogenases (AmDHs), and aminodeoxychorismate lyases (ADCLs) (Koszelewski et al 2011 ; Tufvesson et al 2012 ; Skalden et al 2015 ; Wetzl et al 2016 ; Guo and Berglund 2017 ; Ramsden et al 2019 ; Gavin et al 2019 ; Mangas-Sanchez et al 2020 ). After expressing and rescreening of the enzymes in the form of cell-free extract, we obtained a transaminase ( Vf TA) from Vibrio fluvialis JS17 (PDB: 5ZTX) that can convert (−)-menthone into (+)-neomenthylamine successfully.…”
Section: Resultsmentioning
confidence: 99%
“…Technological advances, in particular genome mining (metagenomics), next generation gene sequencing and bioinformatics, assist the isolation of efficient natural enzyme catalysts. 50,51 Introduction of directed evolution has greatly improved biocatalyst stability and activity. [52][53][54] Computational aided, de novo design has further enhanced the understanding of biocatalysts leading to wider substrate scopes.…”
Section: Summary Of Enzyme Immobilization Methodsmentioning
confidence: 99%
“…Upon examination of the active-site it was found that the transaminase from Pseudovibrio WM33 naturally possessed amino acid substitutions that were introduced into other transaminases to improve reaction rate and melting temperature, showing that metagenomic enzymes can often circumvent tedious engineering efforts. [57] Asymmetric reduction of carbonyls is an essential transformation in biocatalysis. Ketoreductases (KREDs) or alcohol dehydrogenases (ADHs) are able to the reduction of ketones in a wide range of different molecules.…”
Section: C=x Bond Reductionmentioning
confidence: 99%